Nationalism and social policy : the politics of territorial solidarity - Beland, Daniel; Lecours, Andre ([S.l.] : Oxford University Press, USA, 2010)
Despite the recent proliferation of literature on nationalism and on social policy, relatively little has been written to analyze the possible interaction between the two. Scholars interested in social citizenship have indirectly dealt with the interaction between national identity and social programs such as the British NHS, but they have seldom examined this connection in reference to nationalism. Specialists of nationalism rarely mention social policy, focusing instead on language, culture, ethnicity, and religion. The main objective of Nationalism and Social Policy is to explore the nature of the connection between nationalism and social policy from a comparative and historical perspective. At the theoretical level, this analysis will shed new light on a more general issue: the relationships between identity formation, territorial politics, and social policy. Although this book refers to the experience of many different countries, the main cases are three multinational states, that is, states featuring strong nationalist movements: Canada (Quebec), the United Kingdom (Scotland), and Belgium (Flanders). Nationalism and Social Policy looks at the interplay between nationalism and social policy at both the state and sub-state levels through a detailed comparison between these three cases. In its concluding chapter, the book brings in cases of mono-national states (i.e. France, Germany, Sweden, and the United States) to provide broader comparative insight on the meshing of nationalism and social policy. The original theoretical framework for this research is built using insight from selected scholarship on nationalism and on the welfare state.
Keywords: Autonomy and independence movements; Belgium--Flanders; Canada; Great Britain; Public welfare--Political aspects; Scotland; Separatist movements; Social policy